2008
DOI: 10.2306/scienceasia1513-1874.2008.34.245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient inputs on growth, chlorophyll, and tissue nutrient concentration of Ulva reticulata from a tropical habitat

Abstract: "Green tides" caused by overgrowth of Ulva species are an increasing problem in tropical areas. The effect of dissolved nutrients on uptake rates, growth, chlorophyll, and tissue nutrient concentration of Ulva reticulata was examined in laboratory experiments lasting up to 7 d. Sterile seawater was enriched with nitrate, ammonium, phosphate, ammonium + phosphate and nitrate + phosphate. U. reticulata expressed luxury uptake of both nitrogen (N) and phosphorus (P). The maximum N-uptake rate was found when ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…When nutrient enriched, Ulva , an opportunistic alga that has a high uptake rate, can take up large amounts of nutrient, particularly nitrogen (Buapet et al . ). This resulted in a fast growth and an increase of biomass.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When nutrient enriched, Ulva , an opportunistic alga that has a high uptake rate, can take up large amounts of nutrient, particularly nitrogen (Buapet et al . ). This resulted in a fast growth and an increase of biomass.…”
Section: Discussionmentioning
confidence: 97%
“…This result suggested that nutrient availability can facilitate the abundance and growth of early successional species, especially turf and filamentous algae. When nutrient enriched, Ulva, an opportunistic alga that has a high uptake rate, can take up large amounts of nutrient, particularly nitrogen (Buapet et al 2008). This resulted in a fast growth and an increase of biomass.…”
Section: Effects Of Nutrient Enrichmentmentioning
confidence: 99%
“…Three treatments were made: (1) 20: Two-liter CSTR (continuous stirred-tank reactor) with 12rpm stirrer speed was contained with 0.90 gram dry-weight algal biomass (or an algal biomass concentration of 0.45 gram dry-weight per liter). The reactor was fed with unpolluted seawater enriched with ammonium and phosphate at varying concentrations from 10 to 100 µM ammonium and 1 to 10 µM phosphate [3]. The estimated volumetric flow rate of each ammonium and phosphate concentrations was applied.…”
Section: Experimental Designmentioning
confidence: 99%
“…Influent and effluent concentrations monitoring were done until a steady-state condition was achieved which is expected to occur within five days. The initial and final algal biomass concentration was determined in each experimental run [3,6]. Light intensity was monitored once in every run.…”
Section: Experimental Designmentioning
confidence: 99%
“…Hypoxia and algal blooms have been observed along the coastlines of the BOB LME (Buapet et al 2008;Das et al 2004; Lee and Bong 2006;Meybeck and Helmer 1989;Periyanayagi et al 2007). …”
Section: Introductionmentioning
confidence: 99%